Social divides in the age of globalization - Marc Helbling; Sebastian Jungkunz (West European Politics, 2020)
In recent decades, a new integration-demarcation cleavage has emerged in Europe, pitting political parties in favour of globalisation against those opposing globalisation. Although a lot is known about the socio-structural basis and the political organisation of this cleavage, we do not know the extent to which these political divides have led to social divides. Therefore, this article investigates how losers and winners of globalisation oppose each other. On the basis of representative online experiments in Germany and Austria, this article studies attitudes and behaviour towards people with different nationalities, education, and party preferences, which correspond to the cultural, socio-structural, and organisational elements of the new cleavage. More particularly, the extent to which people are willing to interact with each other in daily life and how much they trust each other is investigated. The main results show that people who identify with different parties (especially if they belong to the other side of the cleavage) oppose each other much more strongly than people with different nationalities. There is no divide, however, between the low-skilled and high-skilled. Finally, it appears that the social divides are asymmetrical: the winners of globalisation resent the losers more than the other way round.
doi:10.6084/m9.figshare.10059782.v1
Keywords: 330; cleavages; globalisation; populism; affective; polarisation